Fundamentals of database indexing and searching - Bhattacharya, Arnab (CRC Press, 2015)
Fundamentals of Database Indexing and Searching presents well-known database searching and indexing techniques. It focuses on similarity search queries, showing how to use distance functions to measure the notion of dissimilarity.After defining database queries and similarity search queries, the book organizes the most common and representative index structures according to their characteristics.